mGlu5 Receptors and Relapse to Cocaine-Seeking: The Role of Receptor Trafficking in Postrelapse Extinction Learning Deficits - Lori A. Knackstedt; Marek Schwendt (Neural Plasticity)
We have previously demonstrated that MTEP, an allosteric antagonist of mGlu5, infused into the nucleus accumbens attenuates relapse after abstinence from cocaine self-administration. MTEP infused into the dorsolateral striatum (dlSTR) does not alter relapse but has long-lasting effects on subsequent extinction learning. Here we tested whether systemic MTEP would prevent relapse after abstinence or alter extinction learning. We also investigated the mechanism of action by which intra-dlSTR MTEP on test day alters extinction on subsequent days. Animals self-administered cocaine for 12 days followed by abstinence for 20-21 days. MTEP (0.5–5 mg/kg IP) was administered prior to placement into the operant chamber for a context-primed relapse test. A separate group of animals received intra-dlSTR MTEP prior to the relapse test and were sacrificed day later. Systemic administration of MTEP attenuated abstinent-relapse without significantly affecting extinction learning. Surface biotinylation analysis of protein expression in the dlSTR revealed that, in cocaine animals, intra-dlSTR MTEP administration decreased mGlu5 surface expression and prevented changes in Arc and GluA1/GluA2 observed in their vehicle counterparts. Thus, blockade of mGlu5 receptors may be utilized in future treatment strategies for relapse prevention in humans, although the effects of chronic blockade on extinction learning should be further evaluated.